Answer:
[tex]F_{yx}=3x^{2} cos(xy)- yx^{3} sin(xy)[/tex]
Step-by-step explanation:
We need to find out the partial differential [tex]F_{yx}[/tex] of [tex]F(x,y)=x^{2}sin(xy)[/tex]
First, differentiate [tex]F(x,y)=x^{2}sin(xy)[/tex] both the sides with respect to 'y'
[tex]\frac{d}{dy}F(x,y)=\frac{d}{dy}x^{2}sin(xy)[/tex]
Since, [tex]\frac{d}{dt}\sin t =\cos t[/tex]
[tex]\frac{d}{dy}F(x,y)=x^{2}cos(xy)\times \frac{d}{dy}(xy)[/tex]
[tex]\frac{d}{dy}F(x,y)=x^{2}cos(xy)\times x[/tex]
[tex]\frac{d}{dy}F(x,y)=x^{3}cos(xy)[/tex]
so, [tex]F_y=x^{3}cos(xy)[/tex]
Now, differentiate above both the sides with respect to 'x'
[tex]F_{yx}=\frac{d}{dx}x^{3}cos(xy)[/tex]
Chain rule of differentiation: [tex]D(fg)=f'g + fg'[/tex]
[tex]F_{yx}=cos(xy) \frac{d}{dx}x^{3} + x^{3} \frac{d}{dx}cos(xy)[/tex]
Since, [tex] \frac{d}{dx}x^{m} =mx^{m-1}[/tex] and [tex] \frac{d}{dt} cost =-\sin t[/tex]
[tex]F_{yx}=cos(xy)\times 3x^{2} - x^{3} sin(xy)\times \frac{d}{dx}(xy)[/tex]
[tex]F_{yx}=cos(xy)\times 3x^{2} - x^{3} sin(xy)\times y[/tex]
[tex]F_{yx}=3x^{2} cos(xy)- yx^{3} sin(xy)[/tex]
hence, [tex]F_{yx}=3x^{2} cos(xy)- yx^{3} sin(xy)[/tex]